Globalization and domestic conflict - Michelle R. Garfinkel; Stergios Skaperdas; Constantinos Syropoulos (Center for Economic Studies and ifo Institute (CESifo), 2005)
We examine how globalization affects trade patterns and welfare when conflict prevails domestically. We do so in a simple model of trade, in which a natural resource like oil is contested by competing groups using real resources (?guns?). Thus, conflict is viewed as ultimately stemming from imperfect property-rights enforcement. When comparing autarky with free trade in such a setting, the gains from trade have to be weighed against the possibly higher resource costs of conflict. We find that importers of the contested resource gain unambiguously. By contrast, countries exporting the contested resource will lose under free trade, unless the international price of the resource is sufficiently high. Regardless of what price obtains in international markets, countries tend to over-export the contested resource relative to what we would observe if there were no conflict; for some range of prices, the presence of conflict even inverts the country's comparative advantage. We find further that an increase in the international price of the contested resource over an even wider range reduces welfare, an instance of the ?natural resource curse.?
Keywords: D78; D74; D72; K42; F10; F02; 330; globalization; trade openness; property rights; enforcement; insecurity; conflict; Außenhandelsliberalisierung; Rohstoff; Außenhandel; Rohstoffressourcen; Eigentumsrecht; Politische Unruhen; Bürgerkrieg; Außenhandelseffekt; Wohlfahrtseffekt; Theorie